Smoking and the Pathophysiology of Peripheral Artery Disease - Wang, Weiming; Zhao, Tingting; Geng, Kang; Yuan, Gang; Chen, Yue; Xu, Youhua (Frontiers in Cardiovascular Medicine, 2021)
Smoking is one of the most important preventable factors causing peripheral artery disease (PAD). The purpose of this review is to comprehensively analyze and summarize the pathogenesis and clinical characteristics of smoking in PAD based on existing clinical, in vivo, and in vitro studies. Extensive searches and literature reviews have shown that there is a large amount of data on the pathological process of cigarette smoke and its components affecting PAD through various mechanisms. Cigarette smoke extracts (CSE) can regulate endothelial cell dysfunction, smooth muscle cell remodeling and macrophage phenotype transformation through multiple molecular mechanisms. These pathological changes are the molecular basis for the occurrence and development of peripheral vascular diseases. So far, there is no relevant review, so this review will summarize the latest progress of smoking in regulating PAD through multiple pathways, and its possible pathogenic mechanism.